2013
DOI: 10.1007/s00125-013-2946-5
|View full text |Cite
|
Sign up to set email alerts
|

The loss of Sirt1 in mouse pancreatic beta cells impairs insulin secretion by disrupting glucose sensing

Abstract: Taken together, these findings indicate that in beta cells the deacetylase SIRT1 regulates the expression of specific mitochondria-related genes that control metabolic coupling, and that a decrease in beta cell Sirt1 expression impairs glucose sensing and insulin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 45 publications
2
72
1
Order By: Relevance
“…5B). In contrast, SIRT1 can suppress inflammation and stimulate HSP responses; however, in response to chronic inflammation, similar to that in obesity-associated diabetes, the SIRT1/HUR axis is repressed (Kotas et al 2013), contributing to the unresolved inflammation (LafontaineLacasse et al 2011, Luu et al 2013. In this study, using our in vitro model to mimic in vivo inflammation, we observed that Ala-Gln maintained the HSP70 levels via the SIRT1/HUR axis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…5B). In contrast, SIRT1 can suppress inflammation and stimulate HSP responses; however, in response to chronic inflammation, similar to that in obesity-associated diabetes, the SIRT1/HUR axis is repressed (Kotas et al 2013), contributing to the unresolved inflammation (LafontaineLacasse et al 2011, Luu et al 2013. In this study, using our in vitro model to mimic in vivo inflammation, we observed that Ala-Gln maintained the HSP70 levels via the SIRT1/HUR axis.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, SIRT1 downstream pathways may be suppressed in chronic inflammatory situations, contributing to chronic low-grade inflammation and impaired insulin secretion (Luu et al 2013). Hence, L-glutamine together with L-alanine supplied as the L-alanyl-L-glutamine dipeptide (Ala-Gln) may benefit the antioxidant system, attenuating inflammation, and may modulate the HSP response in catabolic situations (Cruzat et al 2014a,b, Newsholme et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Repression of Sirt 1 in cells is responsible for major intracellular defects and caffeine induced mitochondrial apoptosis relevant to adipogenesis defects [31,32] related to NAFLD with NAFLD to reach 30% of the developing world [159][160][161][162]. Defective hepatic caffeine clearance rates in the developing world may be connected to pancreatic [163][164][165][166][167][168][169][170] and thyroid disease [171][172][173] but xenobiotics may also be the inducing factor in these chronic diseases. LPS induced Sirt 1 repression may involve both caffeine and xenobiotic toxic effects with the induction of NAFLD, NAFLD linked to gall bladder disease [174][175][176][177] and cardiovascular disease [107][108][109].…”
Section: Bacterial Lps and Caffeine Metabolism With Relevance To Naflmentioning
confidence: 99%
“…In addition to regulating glucose metabolism at the level of insulin-target cells, preclinical studies documented that VEGF and SIRT-1 genes act directly on pancreatic beta cells, facilitating insulin release (66, 67). Moreover, a preclinical study demonstrated a direct link between miR-29 and pancreatic insulin release, further connecting this miR with the metabolic adverse effects of APDs (68).…”
Section: Cvae and Metabolic Adverse Effects Of Apds: Same Pathogenesimentioning
confidence: 99%